BILATERAL DEVELOPMENT COOPERATION PROGRAMS BETWEEN THE REPUBLIC OF N. MACEDONIA AND SWEDEN: ALTRUISM OR HIDDEN AGENDA? - Apostolovska stepanoska, Milena; Sofce Krstik (International Academic Institute, 2019)
This paper aim is to indicate the internal motives influencing the shape of the content of Swedish development cooperation policy in the Republic of N. Macedonia. Five universal theoretical models for analysis of the internal motives of the development cooperation policy are developed in the academic area: power-political; political stability and democracy; development and performance; strategic-defensive or Cold War; and economic-commercial. The authors of the research put into context in every each of this theories the most relevant data from the official documents forming the development cooperation policy between Sweden and the Republic of N. Macedonia in order to identify the relevant theoretical model and corresponding motives influencing the content of the Sweden development cooperation policy.